2021
DOI: 10.3389/fpsyg.2021.717960
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Vaccinate Against COVID-19: The Role of Health Locus of Control and Conspiracy Theories

Abstract: Understanding the predictors of the willingness to get vaccinated against COVID-19 may aid in the resolution of current and future pandemics. We investigate how the readiness to believe conspiracy theories and the three dimensions of health locus of control (HLOC) affect the attitude toward vaccination. A cross-sectional study was conducted based on the data from an online survey of a sample of Czech university students (n = 866) collected in January 2021, using the multivariate linear regression models and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 63 publications
2
20
0
Order By: Relevance
“…In this case the intuitive answer is 'first place'; however, of course, if you pass the person in second place then you are in second place [16]. Most of the work using measures of analytic thinking has revealed a small to moderate relationship with conspiracy beliefs [6,9,[17][18][19][20][21][22][23][24][25][26][27][28][29], such that an increased reliance on intuitive thinking is associated with conspiracy beliefs, while analytical thought appears to protect against such beliefs (and some evidence indicates that conspiracy beliefs are more strongly associated with higher intuitive thinking than lower analytic thinking) [30].…”
Section: Dual-process Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case the intuitive answer is 'first place'; however, of course, if you pass the person in second place then you are in second place [16]. Most of the work using measures of analytic thinking has revealed a small to moderate relationship with conspiracy beliefs [6,9,[17][18][19][20][21][22][23][24][25][26][27][28][29], such that an increased reliance on intuitive thinking is associated with conspiracy beliefs, while analytical thought appears to protect against such beliefs (and some evidence indicates that conspiracy beliefs are more strongly associated with higher intuitive thinking than lower analytic thinking) [30].…”
Section: Dual-process Theorymentioning
confidence: 99%
“…Unfounded claims about COVID-19, such as it being a hoax [26] has decreased scientific trust among some individuals and thus curtailed the uptake of preventative measures (e.g., vaccine hesitancy) [43]. The willingness to accept unsupported claims as opposed to health care professionals' recommendations is suggestive of faulty reasoning, or at least a hampered ability to accurately evaluate available evidence.…”
Section: Evidence From Related Domainsmentioning
confidence: 99%
“…Daniel von Wachter performed perhaps one of the most profound social analyses of COVID-19-related conspiracy theories and found that there should be a distinction between “ungrounded” conspiracy beliefs (e.g., SARS-CoV-2 is a special biological weapon) and “rational” conspiracy beliefs (i.e., the system of ideas and corresponding heath behavioral responses of a population) by means of which people try to find logic in administrative steps taken by authorities in the COVID-19 situation and explain them somehow [ 49 ]. Many researchers stress that COVID-19-related conspiracy beliefs are spread like an infodemic because of social network communication [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. A considerable part of conspiracist ideas in different countries is devoted to COVID-19 vaccination and prevention measures associated with using QR (quick response) codes [ 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination has become even more important in suppressing the spread of the COVID-19 pandemic, yet these are cognitive, emotional and social processes that shape the public’s willingness to vaccinate. Vaccination raises many emotions, questions and concerns regarding, among other things, its effectiveness and impact on health [ 20 ]…”
Section: Introductionmentioning
confidence: 99%